2018
DOI: 10.1021/acs.biochem.8b00055
|View full text |Cite
|
Sign up to set email alerts
|

Directed Evolution of Alcohol Dehydrogenase for Improved Stereoselective Redox Transformations of 1-Phenylethane-1,2-diol and Its Corresponding Acyloin

Abstract: Laboratory evolution of alcohol dehydrogenase produced enzyme variants with improved turnover numbers with a vicinal 1,2-diol and its corresponding hydroxyketone. Crystal structure and transient kinetics analysis aids in rationalizing the new functions of these variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 29 publications
0
24
1
Order By: Relevance
“…The kinetic analysis in this study revealed that the enhanced catalytic capability of Q139G mainly originated from the high degree of productive binding rather than from the improved enzyme–substrate affinity. Moreover, the higher K m means lower affinity to the substrate, which might relieve the possible substrate inhibition to some degree [10a, 25a] …”
Section: Resultsmentioning
confidence: 99%
“…The kinetic analysis in this study revealed that the enhanced catalytic capability of Q139G mainly originated from the high degree of productive binding rather than from the improved enzyme–substrate affinity. Moreover, the higher K m means lower affinity to the substrate, which might relieve the possible substrate inhibition to some degree [10a, 25a] …”
Section: Resultsmentioning
confidence: 99%
“…Natural enzymes have been optimized by natural evolution to serve the host organisms' purpose, which does not necessarily coincide with the needs of an organic chemist aiming at the selective oxidation of a given target molecule. Next to screening natural diversity for more suitable enzymes, protein engineering has become a very powerful tool to tailor the properties of a given enzyme such as cofactor specificity, thermo and solvent stability, (enantio)selectivity, and more [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Substrate Scopementioning
confidence: 99%
“…Specifically, increases in the K m value was observed with a simultaneous increase in the k cat value for substrates 1 a when the mutant Q139S/V187S was used as a catalyst. This result revealed that the improved catalytic capability of Q139S/V187S toward substrate 1 a was mainly originated from the high degree of productive binding but not from the enhanced enzyme‐substrate affinity [13b,17] . It is obviously different from the determined kinetic parameters of the mutant Q139S/V187S toward halogenated α‐tetralones ( 2 a , 4 a and 5 a ), indicating the halogen substitution at aromatic ring of the substrates result in distinct effects on enzyme‐substrate binding.…”
Section: Resultsmentioning
confidence: 82%